Ecology and Biodiversity of Crop Pest of Various Genera of Order Rodentia Inhabit District Dadu, Sindh, Pakistan - Badaruddin Gorar; Ayaz Hussain Qadri; Sajid Siyal; Fiza Bano; Sheeraz Qadri (Dialogue Social Science Review (DSSR), 2024)
Rodents are mammals which belong to the order Rodentia, they are characterized by a single pair of continuously growing incisors in each of the upper and lower jaws. About 40% of all mammal species are rodents; they are found on all continents in vast number except Antarctica. They are the most diversified mammalian order and live in a variety of terrestrial habitats, including human-made environments. The information related to the existence of different species of order rodentia was collected from local community of District Dadu from March 2017 to February 2018 to All collected specimens were brought to vertebrate laboratory and were examined carefully. All specimens were identified with the help of identification key and relevant literature. The morphological characteristics included Body weight, Length of body, length of tail, length of hind limb, length of ear. This investigation recorded species 05 species Rattus rattus Rattus norvegicus Mus booduga Sacista concolor and Apodemus sylvaticus 02 Sub-species Rattus Rattus Rattus and Rattus Rattus Fugivorous belonging to different genera under order Rodentia from different localities of District Dadu. All together 284 specimens were collected, out of which 96 specimens were of R. rattus 41 males 55 females 91 specimens were of R. norvegicus 40 males 51 females 14 specimens were of M. booduga 05 male 09 females 12 specimens were of S. concolor 5 female 7 males 71 specimens were of A. Sylvaticus 32 males 39 females and out of 96 specimens of Rattus rattus 08 specimens were subspecies of R. r. rattus 03 males 05 females and 09 specimens were of R. r. fugivorous 05 males 04 females.